2021
DOI: 10.1038/s41598-021-99034-0
|View full text |Cite
|
Sign up to set email alerts
|

Some socially poor but also some socially rich adolescents feel closer to their friends after using social media

Abstract: Who benefits most from using social media is an important societal question that is centered around two opposing hypotheses: the rich-get-richer versus the poor-get-richer hypothesis. This study investigated the assumption that both hypotheses may be true, but only for some socially rich and some socially poor adolescents and across different time intervals. We employed a state-of-the-art measurement burst design, consisting of a three-week experience sampling study and seven biweekly follow-up surveys. Person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Meanwhile, we found support for the coexistence of social compensation and social enhancement effects in the relationship between initial service leadership qualities and posttest PYD qualities. This observation echoes a prior proposal of the coexistence of these two effects in social media use (Pouwels et al, 2021 ; Wang et al, 2018). It is possible that online SL provides students who are relatively left behind in the initial service leadership qualities with opportunities for meaningful social interactions with teachers, classmates, and particularly service recipients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, we found support for the coexistence of social compensation and social enhancement effects in the relationship between initial service leadership qualities and posttest PYD qualities. This observation echoes a prior proposal of the coexistence of these two effects in social media use (Pouwels et al, 2021 ; Wang et al, 2018). It is possible that online SL provides students who are relatively left behind in the initial service leadership qualities with opportunities for meaningful social interactions with teachers, classmates, and particularly service recipients.…”
Section: Discussionsupporting
confidence: 90%
“…However, loneliness was not associated with frequency of social media use, and social anxiety was not associated with online social capital. In view of these inconsistent findings, a few scholars (e.g., Pouwels et al, 2021 ; Wang et al, 2018) contended that these two hypotheses were not necessarily mutually exclusive. It is possible that both high-competent and low-competent individuals (relative to medium–competent ones) receive the most benefits from social media use.…”
Section: Who Benefits More From Online Sl?mentioning
confidence: 99%
“…Not only was the rich-get-richer hypothesis unsupported, but more personal disclosure in masspersonal CMC was associated with poorer social connectedness, and in turn less positive subjective well-being for the socially rich. Although unexpected, these findings are consistent with a very recent report in which psychosocial outcomes were compared between the socially rich and poor as determined by their level of loneliness (Pouwels et al, 2021b). They found that adolescents who were less lonely were more likely to experience decreases in friendship closeness after using social media than lonelier peers.…”
Section: Discussionsupporting
confidence: 89%
“…It is the person who is interested in social interactions but who shies away from them that has driven interest in CMC as a potential compensatory tool. Alongside introverted (Dolev-Cohen & Barak, 2013), lonely (Pouwels et al, 2021b) and those with low self-esteem (Valkenburg et al, 2017), people who desire but avoid social interactions can be conceptualized as socially anxious (Lundy & Drouin, 2016). Because of the prevalence of relatively high levels of social anxiety in the general population (about one in three individuals; Jefferies & Ungar, 2020) and the potential of CMC to compensate for their interpersonal difficulties, the current study considered if those with high (or low) social anxiety benefit most from their online self-disclosure.…”
Section: Social Benefits Associated With Positive Online Self-disclosurementioning
confidence: 99%
“…Other social partners may also have been important sources of support for the adolescents in our study (e.g., the peer group, grandparents, teachers, sports coach). Additionally, whereas there are indications that social media use may affect both relationship quality and adolescent adjustment during the COVID-19 pandemic (Ellis et al, 2020;Pouwels et al, 2021), social media use was not included in our study. However, these aspects of social contact lay beyond the scope of the present study.…”
Section: Quaranteens: Social Relationships and Adolescent Problems Du...mentioning
confidence: 99%